2016
DOI: 10.21315/mjms2016.23.5.6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Unmet Needs among the Elderly Residents of the rural Field Practice Area of a Tertiary Care Centre from Northern India

Abstract: To cite this article: Singh A, Bairwa M, Goel S, Bypareddy R, Mithra P. Practical area of tertiary care centre from Northern India. Abstract Background: Surrogate markers simple enough to be used by primary care workers have not been closely investigated by the community experts in rural Uttar Pradesh. We assessed the physical disabilities in activities of daily living (ADL) and unmet need in physical disabilities among rural elderly. Predictors of unmet needs in physical disabilities among the elderly were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…Surprisingly, being married or cohabiting was positively associated with unmet need in multivariate analysis. At first sight, this finding does not align with results from other studies that have found more unmet needs in people who live without a spouse than in those sharing their household with a spouse ( Harling et al, 2020 ; Singh et al, 2016 ). However, unmet need in this case might also be either the result of the limited informal caregivers’ ability to fulfill the need of the disabled person or a wish on the part of the care recipients to minimize the burden placed on carers by their care need ( Choi & McDougall, 2009 ).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Surprisingly, being married or cohabiting was positively associated with unmet need in multivariate analysis. At first sight, this finding does not align with results from other studies that have found more unmet needs in people who live without a spouse than in those sharing their household with a spouse ( Harling et al, 2020 ; Singh et al, 2016 ). However, unmet need in this case might also be either the result of the limited informal caregivers’ ability to fulfill the need of the disabled person or a wish on the part of the care recipients to minimize the burden placed on carers by their care need ( Choi & McDougall, 2009 ).…”
Section: Discussioncontrasting
confidence: 95%
“…Among those with any ADL impairment, middle-aged people reported significantly higher rates of unmet need than older individuals. While older age has been found to be associated with unmet need in Nigeria ( Gureje et al, 2006 ) and India ( Singh et al, 2016 ), studies in Zimbabwe and South Africa revealed a similar reversed age gradient ( Allain et al, 1997 ; Harling et al, 2020 ). Middle-aged people with ADL impairment possibly receive care from their parents, who might not be able to fulfill the individuals’ needs as well as it would be the other way around.…”
Section: Discussionmentioning
confidence: 97%
“…Few other studies have addressed the issue of unmet need for care in LMICs, and most have examined perceived rather than evaluated unmet need. Results from India suggest rates of unmet need of approximately a third of those aged 60 years and above in a rural setting ( Singh, Bairwa, Goel, Bypareddy, & Mithra, 2016 ), although this analysis included unmet need for instrumental as well as basic ADLs. In China, rates of 50% to 65% were reported from a study of those aged 80 years and above in rural and urban settings ( Zhu, 2015 ); this analysis combined partially met need with unmet need however, and variations in definitions are likely to have led to this high figure.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported in the Manipur study, that 60.8% were financially dependent and in a similar study, financial dependency was found among 27.3% males and 63.6% females. 12,17 In another study, it was 58.5% for financially dependency of elderly. 19 Regarding addiction habits, most (75.6%) had stated nil in this study.…”
Section: Discussionmentioning
confidence: 93%
“…their inability to work. 17,18 The inability status of elderly to work is a physiological phenomenon, but the consequences may lead to a state of financial dependency. Also, lack of individual income as reported by males (8%) and females (20%) could be taken as financial dependency.…”
Section: Discussionmentioning
confidence: 99%